Biogenesis of silver nanoparticles using leaf extract of Turnera ulmifolia Linn. and screening of their antimicrobial activity - Shekhawat, M S; Kannan, N; Manokari, M (Journal of Ecobiotechnology, 2012)
Development of nontoxic and clean techniques for the synthesis of silver nanoparticles (Ag NPs) has attracted increasing attention in recent years. The biological synthesis of silver nanoparticles using Turnera ulmifolia plant leaf extract was studied in present investigation. The synthesized nanoparticles were confirmed by color changes from pale green to reddish brown and characterized by UV-Visible spectrophotometer. A peak between 415 nm to 425 nm was obtained on spectrometer characterized the biosynthesis of silver nanoparticles. The synthesized nanoparticles also showed antibacterial activity against four disease causing microorganisms.